ANALISIS PENGARUH CITRA MEREK, KUALITAS LAYANAN, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN JASA (Studi pada pengguna jasa freight forwarder di DHL Global Forwarding Semarang Branch) - Hessy, Via; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2015)
The problem of this study is the number of user-level services at DHL Global Forwarding Semarang Branch which tend to decrease from year to year. It is influenced by the intense competition in the business of freight forwarders. This study aims to examine and analyze how the influence of brand image, quality of service, and the promotion of the use of decision DHL Global Forwarding services and to identify and analyze the most dominant factor affecting the use of the decision. This study tested the brand image (X1), Quality of Service (X2), and Promotion (X3) which affects the purchasing decision (Y)The population in this study is the consumer service users DHL Global Forwarding. Samples were taken of 100 respondents, the sampling technique used was non-probability sampling technique. The analytical method used is quantitative analysis is multiple regression analysis. From the analysis, obtained the following results:Y = 0.169 X1 + 0.405 X2 + 0.339 X3Where all the independent variables have a positive and significant impact on purchasing decisions (Y). Adjusted R Square value is 0,504. It can be concluded that the ability variable brand image, quality of service and promotion in explaining variation in the dependent variable is the purchase decision of 50.4% and the remaining 49.6% is influenced by other variables.